Anisotropic silicon nanowire arrays fabricated by colloidal lithography. Issue 12 (20th May 2021) - Rey, Marcel; Wendisch, Fedja Jan; Aaron Goerlitzer, Eric Sidney; Julia Tang, Jo Sing; Bader, Romina Sigrid; Bourret, Gilles Remi; Vogel, Nicolas
Abstract : We demonstrate the design of silicon nanowire arrays with tunable elliptical cross-sections. Their anisotropic character of the individual pillars affords defined bending or bundling of the arrays. Abstract : The combination of metal-assisted chemical etching (MACE) and colloidal lithography allows for the affordable, large-scale and high-throughput synthesis of silicon nanowire (SiNW) arrays. However, many geometric parameters of these arrays are coupled and cannot be addressed individually using colloidal lithography. Despite recent advancements towards higher flexibility, SiNWs fabricated via colloidal lithography and MACE usually have circular, isotropic cross-sections inherited from the spherical templates. Here we report a facile technique to synthesize anisotropic SiNWs with tunable cross-sections via colloidal lithography and MACE. Metal films with an elliptical nanohole array can form from shadows of colloidal particles during thermal evaporation of the metal at tilted angles. The aspect ratio of these anisotropic holes can be conveniently controlled via the deposition angle. Consecutive MACE using these patterned substrates with or without prior removal of the templating spheres results in arrays of anisotropic SiNWs with either elliptical or crescent-shaped cross-sections, respectively. As a consequence of the anisotropy, long SiNWs with elliptical cross-sections preferentially collapse along their short axis, leading to a controlled bundling process and the creation of anisotropic surface topographies. These results demonstrate that a rich library of SiNW shapes and mesostructures can be prepared using simple spherical colloidal particles as masks.